Lean Management in the Banking Industry: A Case Study - Grozdić, Vanja; Demko-Rihter, Jelena; Benković, Slađana (International Journal of Industrial Engineering and Management, 2023)
The purpose of this paper is to discuss the application of lean principles in the banking industry. The difference between AS-IS and TO-BE process parameters represented the main effects of the improved process using lean tools such as value stream mapping, as well as lean techniques such as centralization, rearranging, elimination, and automation of the process activities. The results showed that lean implementation leads to better overall process performance expressed by various parameters, such as lead time, waiting time, processing time, and process efficiency. Additionally, the Wilcoxon signed-rank test results confirmed that the banking process improved by lean (TO-BE), compared to the existing process (AS-IS), has a shorter duration, and that the positive difference between AS-IS and TO-BE process duration is statistically significant. Also, the effect size based on the mean comparison showed that this statistically significant difference is not trivial. The study demonstrates how banks, relying on the lean paradigm, can improve operational efficiency, but also cope with intense competition, maintain market share, save operating costs, and attract new clients. Article history: Received (July 3, 2023); Revised (September 29, 2023); Accepted (November 28, 2023); Published online (December 5, 2023)